Analisis Manajemen Hubungan Masyarakat di Sekolah Dasar - Ira Wati Subandi; Sri Marmoah (Jurnal Ilmiah Dikdaya, 2026)
This study analyzes public relations management at SDN 1 Jungakre Klaten as an effort to strengthen collaboration among the school, parents, and the community to improve the quality of learning. The research is grounded in the importance of the community’s role as a facilitator, partner, and learning resource that supports educational goals. A qualitative approach with a case study design was employed to explore public relations practices in depth. Data were collected through participatory observation, in-depth interviews with the principal, public relations staff, teachers, and the school committee, as well as documentation of activity records. Data analysis was conducted inductively through the processes of reduction, presentation, and conclusion drawing, with validity reinforced by source and method triangulation. The findings show that the active involvement of parents and the community—such as local farmers serving as resource persons—enhances students’ motivation and academic achievement while enriching contextual learning experiences. The planning, implementation, and evaluation of public relations programs that engage multiple stakeholders foster harmonious two-way communication and a sense of ownership toward the school. Joint evaluations with the school committee strengthen continuous improvement efforts and cultivate a collaborative culture.